PENGARUH LAYANAN INFORMASI FORMAT KLASIKAL DENGAN TEKNIK MODELING SIMBOLIK TERHADAP MANAJEMEN WAKTU BELAJAR SISWA KELAS X MIPA 1 DI SMAN 3 KOTA BENGKULU - Novri Hemdi Saputra; Yessy Elita; Sri Saparayuningsih (UNIVERSITAS BENGKULU, 2022)
Abstract This study aims to describe the effect of classical information services with symbolic modeling techniques on learning time management. The method used is an experiment with a one-group design, pre test-post test design. The population taken was 148 class X MIPA and the sample in this study was class X MIPA 1 SMA Negeri 3 Bengkulu City totaling 32 students. The sampling procedure used purposive sampling. The data collection technique uses a questionnaire with a Likert model scale. Data analysis techniques using the t test. The results of this study proved that student learning time management increased after being given information services. The results of the pre-test and post-test differences with a t value of -29.254 and a significance level of 0.000 (p <0.005) so that the hypothesis (Ho) is rejected and (Ha) is accepted. The average student learning time management before being given treatment is in the low category and after being given treatment the average value becomes in the high category. This study also proves that information services using symbolic modeling techniques are effective for improving student time management in class X MIPA 1 students at SMA Negeri 3 Bengkulu City. Based on the results of this study, it is suggested that counseling teachers to overcome the problem of learning time management can use classical format information services with symbolic modeling techniques. Keywords: Learning Time Management, Information Service, Symbolic Modeling